Novel biocomposite from polyamide 11 and jute fibres: the significance of fibre modification with SiO2 nanoparticles. Issue 3 (9th November 2021) - Van Cong, Do; Giang, Nguyen Vu; Trung, Tran Huu; Tuan, Pham Quoc; Thai, Nguyen Thi; Tham, Do Quang; Van Tien, Mai; Quang, Dang Viet
Abstract: Jute fibres (JFs) and polyamide 11 (PA11) are naturally originated materials that, individually, have been widely employed for the manufacture of biocomposites. However, their simultaneous use in an environmentally friendly JFs/PA11 biocomposite that combines the advantages of both materials has received little attention. Therefore, this study investigated the possible fabrication of a biocomposite based on JFs and PA11. Since the dispersion, adhesion and interfacial interaction between JFs and resin matrix are usually poor, the possibility of improving those characteristics was explored via chemical modification. Accordingly, two modification routes were used: alkali treatment and SiO2 nanoparticle deposition. Both modified and unmodified fibres were blended with PA11 for biocomposite production. Various techniques including Fourier transform infrared spectroscopy, thermogravimetry, mechanical property analysis and scanning electron microscopy were used to characterize fibre and biocomposite samples. The results indicated that thermal and mechanical stability of JFs were considerably improved as a result of modification. The tensile strength and Young's modulus of unmodified fibres was 303.75 MPa and 12.32 GPa, which then increased to 483.66 MPa and 483.66 GPa, respectively, as a result of SiO2 nanoparticle deposition on the fibre surface. Because of SiO2 nanoparticle modification, the interaction and adhesion between JFs and PA11 matrix were improved, which led to increases of 58.3%, 11.7% and 45.9% in tensile strength, impact strength and Young's modulus. The success of this study provides a novel route to produce a complete biocomposite from JFs and PA11, which could become a promising alternative to conventional synthetic polymer composites. © 2021 Society of Industrial Chemistry. Abstract : A novel biocomposite based on jute fibres and polyamide 11 was successfully prepared using a moulding compression method. The tensile strength and Young's modulus of the resulting composite were improved by 58.3% and 45.9% when jute fibres were modified with SiO2 nanoparticles.